Genealogy of Counterfeit Goods: The Indonesian Experience - Damsar, Damsar (LPPM Universitas PGRI Sumatera Barat, 2022)
The purpose of this study is to find the genealogy of counterfeit goods from the Indonesian experience. This study uses genealogy as a method for understanding discourse, whether it is written in the library or spoken in terms of proverbs, words of wisdom, or social praxis that has become local wisdom. The genealogy of counterfeit goods in Indonesia was inseparable from the historical roots of global capitalism which were embedded through Auteurswet 1912. The term counterfeit goods is related to copyright and intellectual property rights in positive law vis a vis local wisdom and the socio-cultural history of indigenous peoples is related to imitative goods.